Role of Western Academia in Victimization of Muslims Post 9/11 Scenario - Maira F. Maneka (Al-Qanṭara, 2023)
This paper tries to examine the Muslim experience of social violence and the role of Western academia in perpetuating it, after the event of 9/11. The paper is divided into three parts. First it explores social violence on Muslims, followed by a section on how representations of Muslims are possible causes of it. Lastly the paper discusses how academia reduces the understanding of Islam and Muslims to extremism through the use of non-contextual reductionist discourse, biased pairing of terms and subordination to the ultimate attribution error.